Reduced angiopoietin-2 as a predictive biomarker for clomiphene citrate resistance in polycystic ovary syndrome - Luxmipratha Rajendiran; Hanumanthappa Nandeesha; Thyagaraju Chitra (Wolters Kluwer Medknow Publications, 2021)
Background: Even though angiopoeitin-2 and interleukin (IL)-23 are known to be altered in polycystic ovary syndrome (PCOS), their association with clomiphene citrate (CC) resistance has not been studied. Aim: The objective of the study was to investigate whether angiopoietin-2 levels are associated with inflammation and CC resistance in PCOS. Settings and Design: This study was conducted in a tertiary care hospital. Materials and Methods: Eighty-one women diagnosed with PCOS and on treatment with CC were enrolled in the study. Angiopoeitin-2 and IL -23 were analyzed in all the subjects. Results: Angiopoietin-2 was significantly reduced (P = 0.018), and body mass index (BMI) (P = 0.049) and duration of infertility (0.006) were significantly increased in PCOS women with CC resistance compared to those who are sensitive to CC. In CC resistant PCOS, IL-23 predicts reduction in angiopoietin-2 levels (P = 0.010). Among angiopoietin-2, IL-23, BMI, and duration of infertility, we found that angiopoeitn-2 (P = 0.020) and duration of infertility (0.036) can predict resistance to CC therapy among PCOS subjects. Conclusion: We conclude that reduced angiopoietin-2 levels predict CC resistance in women with PCOS.